IMPLEMENTASI POLA PEMBINAAN ANAK MENURUT RASULULLAH SAW DI MASYARAKAT MUSLIM PATTANI THAILAND - Sidek, Hannah; Hafid, Erwin; Amri, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2018)
The process of fostering children has an important role in the world of education, but there are many problems related to this pattern of formation, especially in terms of morality. At this time, along with the shifting of social institutions that have resulted in immoral acts and violence in all aspects of people's lives, it is necessary to protect or foster children's rights especially children in the Thai Pattani Muslim community, by observing the activities of the Thai Pattani Muslim community in maintaining or giving guidance to children. This paper discusses the Pattern of Child Development according to the Messenger of Allah. in the Thai Pattani Muslim Community. The implications of this study indicate that the attitudes and behavior of parents will be imitated directly by their children and that it will become a habit for children. So from this research is expected to provide knowledge and benefits to all parents in improving the pattern of child development according to the Prophet. so that children can live in Islamic culture.